‘PUBLIC SPEAKING’ SEBAGAI BAGIAN DARI KOMUNIKASI EFEKTIF (KEGIATAN PKM di SMA KRISTOFORUS 2, JAKARTA BARAT) - Girsang, Lasmery Rosentauly Maissalinya (Universitas Bunda Mulia, 2018)
ABSTRACT Everyone is able to speak, but only some who are able to gather words into beautiful language and can attract the public to hear it. So, simply speaking public speaking means the ability to speak by